The Library’s Impact on University Students’ Academic Success and Learning - Scoulas, Jung Mi; De Groote, Sandra L. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2019)
Objective – The purpose of this study was to examine relationships among student library visits, library resource use, library space satisfaction (e.g., quiet study space), and students’ academic performance (i.e., Grade Point Average or GPA) using quantitative data and to better understand how the academic library has an impact on students’ learning from students’ perspectives using qualitative data.Methods – A survey was distributed during the Spring 2018 semester to graduate and undergraduate students at a large public research institution. Survey responses consisted of two types of data: (1) quantitative data pertaining to multiple choice questions related to the student library experience, and (2) qualitative data, including open-ended questions, regarding students’ perceptions of the library’s impact on their learning. Quantitative data was analyzed using Spearman’s rank correlations between students’ library experience and their GPAs, whereas qualitative data was analyzed employing thematic analysis.Results – The key findings from the quantitative data show that student library visits and library space satisfaction were negatively associated with their GPA, whereas most students’ use of library resources (e.g., journal articles and databases) was positively associated with their GPAs. The primary findings from the qualitative data reveal that students perceived the library as a place where they can concentrate and complete their work. Additionally, the students reported that they utilize both the quiet and collaborative study spaces interchangeably depending on their academic needs, and expressed that the library provides them with invaluable resources that enhance their coursework and research.Conclusions – While the findings show that the student library experience was associated with their academic achievements, there were mixed findings in the study. The findings suggest that as a student’s GPA increases, their in-person library visits and library space satisfaction decrease. On the other hand, as a student’s GPA increases, their library resource usage increases. Further investigation is needed to better understand the negative relationship between students’ library visits, library space satisfaction, and their GPAs.